Respostas
respondido por:
0
Espero ter ajudado. :))
respondido por:
0
a2-a1 =r
a3-a2=r
a4-a3= r
....
Ou seja,(a partir do segundo termo),o termo posterior menos o termo antecessor é igual a razão.
(11/6) - (1/2) :
Fazendo mmc
(11/6)2 - (1/2)/6
22 - 6/12 = 16/12
Simplificando:
r= 4/3
a3-a2=r
a4-a3= r
....
Ou seja,(a partir do segundo termo),o termo posterior menos o termo antecessor é igual a razão.
(11/6) - (1/2) :
Fazendo mmc
(11/6)2 - (1/2)/6
22 - 6/12 = 16/12
Simplificando:
r= 4/3
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás